THE PROCESS OF WOUND HEALING IN POST SECTIO CAESAREA PATIENTS USING NORMAL SALINE (0.9%) AND POVIDONE-IODINE (10%) IRRIGATIONS: A COMPARATIVE STUDY - Dedi Kurnia; Restuning Widiasih; Urip Rahayu (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2022)
Surgical Site Infection (SSI) is a complication after surgery, and one of the causes is the use of intra-operative irrigation fluids. The most common irrigation fluid was 0.9% Normal Saline and 10% Povidone-Iodine in several hospitals in Indonesia. However, the difference in composition has not been observed for its effect on wound healing. This study aimed to determine the difference in using 0.9% Normal Saline and 10% Povidone-Iodine for irrigation in the wound healing process for post-cesarean patients. The research design used is a descriptive comparative study with ex post facto approaches. Due to the COVID-19 pandemic, researchers changed the data collection method from direct observations to analyzing secondary data post-cesarean surgery data in 2019. The study was conducted in a referral hospital in West Java Province, Indonesia. The sampling used non-probability sampling with a purposive sampling technique. The sample was 440 patient medical records. These records consisted of 0.9% Normal Saline irrigation fluid, 140 respondents, and 10% Povidone-Iodine irrigation fluid, 300 respondents. The chi-square analysis showed significant differences in the two types of intra-operative wound irrigation (0.9% Normal Saline and 10% Povidone-Iodine) with a wound healing process (P-value = 0.021). The distribution frequency showed that the infection of 0.9% Normal Saline fluid was 5% of the 133 respondents, and 10% Povidone-Iodine was 12% out of 300 respondents. The study results showed that 0.9% Normal Saline and 10% Povidone-iodine could be used for intra-operative wound irrigation with different characteristics and compositions that impact the postoperative wound healing process. There is a need for further research to do a direct observation to test the effectiveness of two types of irrigation fluids from intra-operative to postoperative and assess other influencing factors.